Brushes and lamellar mesophases of comb-shaped (co)polymers: a self-consistent field theory. Issue 40 (13th October 2020) - Mikhailov, Ivan V.; Zhulina, Ekaterina B.; Borisov, Oleg V.
Abstract : Superimposed distributions of main chain ends in brush of comb polymers with different length and grafting density of side chains. Abstract : Theory describing equilibrium structural properties of solvent-free brushes formed by comblike polymers tethered by end segment of backbone to planar surface is developed using strong-stretching self-consistent field (SS-SCF) analytical approach and supported by numerical self-consistent field calculations based on the Scheutjens–Fleer (SF-SCF) method. The explicit dependence of self-consistent molecular potential on architectural parameters of comblike polymers is analyzed. It is demonstrated that distribution of local tension in backbones of long comblike polymers approaches that for linear chains. The star-to-comblike transition in solvent-free lamellas which occurs upon increase of backbone length of graft-polymer is analyzed.